Ion Channels of Pituitary Gonadotrophs and Their Roles in Signaling and Secretion - Stojilkovic, Stanko S.; Bjelobaba, Ivana; Zemkova, Hana (Frontiers in Endocrinology, 2017)
Gonadotrophs are basophilic cells of the anterior pituitary gland specialized to secrete gonadotropins in response to elevation in intracellular calcium concentration. These cells fire action potentials spontaneously, coupled with voltage-gated calcium influx of insufficient amplitude to trigger gonadotropin release. The spontaneous excitability of gonadotrophs reflects the expression of voltage-gated sodium, calcium, potassium, nonselective cation-conducting, and chloride channels at their plasma membrane. These cells also express the hyperpolarization-activated and cyclic nucleotide-gated cation channels at the plasma membrane, as well as GABAA, nicotinic, and purinergic P2X channels gated by GABA, acetylcholine, and ATP, respectively. Activation of these channels leads to initiation or amplification of the pacemaking activity, facilitation of calcium influx, and activation of the exocytic pathway. Gonadotrophs also express calcium-conducting channels at the endoplasmic reticulum membranes gated by inositol trisphosphate and intracellular calcium. These channels are activated potently by hypothalamic gonadotropin-releasing hormone and less potently by several paracrine calcium-mobilizing agonists, including pituitary adenylate-activating peptides, endothelins, acetylcholine, vasopressin and oxytocin. Activation of these channels causes oscillatory calcium release and a rapid gonadotropin release, accompanied with a shift from tonic firing of single action potentials to periodic bursting type of electrical activity, which accounts for a sustained calcium signaling and gonadotropin secretion. This review summarizes our current understanding of ion channels as signaling molecules in gonadotrophs, the role of gonadotropin-releasing hormone and paracrine agonists in their gating, and the crosstalk among channels.